Konsep Khulu’ dalam Al-Qur’an: Analisis Tafsir Surah Al-Baqarah Ayat 229 Perspektif Al-Tabari dan M.Quraish Shihab - Irda Djesra Mukhdalifa; Faisal Hamdani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Divorce is recognized in Islam as a lawful but final solution when marital harmony can no longer be maintained. One form of divorce is khulu’, namely the dissolution of marriage initiated by the wife through compensation to the husband under certain conditions. Despite the increasing number of divorce cases, studies examining the concept of khulu’ from the perspective of Qur’anic exegesis remain relatively limited. This study aims to analyze the interpretation of Surah Al-Baqarah verse 229 concerning khulu’ according to Imam Al-Tabari and M. Quraish Shihab, as well as to identify the similarities and differences in their interpretative approaches. This research employs a qualitative method with a library research approach. The primary data consist of Jāmi‘ al-Bayān ‘an Ta’wīl Āy al-Qur’ān by Imam Al-Tabari and Tafsir Al-Misbah by M. Quraish Shihab, while secondary data are obtained from books, scientific journals, fiqh literature, and other relevant references. The findings indicate that both exegetes agree that khulu’ is a legitimate mechanism in Islamic law that grants women the right to terminate a marriage when it no longer realizes justice and mutual welfare. However, Al-Tabari emphasizes historical narrations, legal arguments, the condition of nusyuz, and the permissibility of compensation (‘iwadh) from the wife, whereas Quraish Shihab highlights the ethical values of justice, public welfare (maslahah), and the protection of women's rights within marriage. Therefore, the concept of khulu’ in the Qur’an reflects a balanced legal instrument designed to uphold justice and safeguard the dignity and rights of both spouses in marital life.